Development of Urban Heat Island e-module for high school student in Surakarta City, Indonesia - Siti Azizah Susilawati (Tanjong Malim, 2024)
Development of Urban Heat Island e-module for high school student in Surakarta City, Indonesia by Siti Azizah Susilawati